2013
DOI: 10.1021/cs400706e
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Kinetic Study on the Zeolite-Catalyzed Benzene Methylation in ZSM-5

Abstract: The methylation of arenes is a key step in the production of hydrocarbons from methanol over acidic zeolites. We performed ab initio static and molecular dynamics free energy simulations of benzene methylation in H-ZSM-5 to determine the factors that influence the reaction kinetics. Special emphasis is given to the effect of the surrounding methanol molecules on the methylation kinetics. It is found that for higher methanol loadings, methylation may also occur from a protonated methanol cluster, indicating tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
112
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(117 citation statements)
references
References 75 publications
5
112
0
Order By: Relevance
“…[27][28][29][30][31][32][33][34][35][36][37] Only a limited number of studies have applied techniques that go beyond the static approach to describe chemical transformation in zeolites. [19,20,[38][39][40][41][42][43][44] The strength of a dynamical approach was earlier demonstrated by some of the present authors.We reported that the influence of the presence of multiple protic molecules on the methylation of benzene [44] and methoxide formation [42] in H-ZSM-5 has to be studied with molecular dynamics. These studies demonstrated that formation of protonated clusters of protic molecules has to be taken into account when modeling reactions under conditions of high reactant loadings, in particular in case of protic reactants that can play a solvent-like role.…”
supporting
confidence: 66%
See 4 more Smart Citations
“…[27][28][29][30][31][32][33][34][35][36][37] Only a limited number of studies have applied techniques that go beyond the static approach to describe chemical transformation in zeolites. [19,20,[38][39][40][41][42][43][44] The strength of a dynamical approach was earlier demonstrated by some of the present authors.We reported that the influence of the presence of multiple protic molecules on the methylation of benzene [44] and methoxide formation [42] in H-ZSM-5 has to be studied with molecular dynamics. These studies demonstrated that formation of protonated clusters of protic molecules has to be taken into account when modeling reactions under conditions of high reactant loadings, in particular in case of protic reactants that can play a solvent-like role.…”
supporting
confidence: 66%
“…The effect of this phenomenon on activation barriers was recently demonstrated by some of the present authors. [42,44] For the methylation of benzene in H-ZSM-5 it was found that after framework deprotonation, protonated hydrogen bonded methanol clusters are formed, which are less reactive towards methylation compared to single protonated methanol molecules. These protonated clusters of protic molecules could be observed as well during our simulations (Table S5.1).…”
Section: Proton Mobilitymentioning
confidence: 99%
See 3 more Smart Citations